2006
DOI: 10.1007/s10672-005-9003-6
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Legal Environment: How Stigma Influences Invisible Identity Groups in the Workplace

Abstract: Diversity research assumes that social interaction is influenced by a social categorization that arises from visible and readily detectable differences. How does this process work when the differences are not readily detectable? We explore the legal protections that shape the employment environment for people with invisible identities and how invisibility influences the common social dimensions of stigma these individuals experience. These social dimensions are resistant to change and therefore change occurs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 38 publications
1
78
0
5
Order By: Relevance
“…Bowen and Blackmon (2003) suggested that "managing 'invisible diversity' may be just as crucial as (managing) 'visible diversity'… but provides additional challenges since individuals may choose to conceal or evade, rather than speak up about their differences" (p. 1395). The option to conceal one's sexual orientation is sometimes used strategically (see Creed, 2003), but, as we will discuss, concealment comes with a host of negative consequences for both individuals and the organizations that employ them (Beatty & Kirby, 2006;Day & Schoenrade, 1997;Ragins & Cornwell, 2001;Rostosky & Riggle, 2002).…”
Section: Sexual Orientation As An (Invisible) Aspect Of Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bowen and Blackmon (2003) suggested that "managing 'invisible diversity' may be just as crucial as (managing) 'visible diversity'… but provides additional challenges since individuals may choose to conceal or evade, rather than speak up about their differences" (p. 1395). The option to conceal one's sexual orientation is sometimes used strategically (see Creed, 2003), but, as we will discuss, concealment comes with a host of negative consequences for both individuals and the organizations that employ them (Beatty & Kirby, 2006;Day & Schoenrade, 1997;Ragins & Cornwell, 2001;Rostosky & Riggle, 2002).…”
Section: Sexual Orientation As An (Invisible) Aspect Of Diversitymentioning
confidence: 99%
“…Some GLBT employees construct heterosexual partners, bring opposite-sex friends as pretend partners to company events, and spend considerable energy trying to avoid speaking of their real, same-sex partners while at work (Özbilgin & Woodward, 2003). Such concealment detracts from constructive, productive behaviors (see Beatty & Kirby, 2006). Hewlin (2009) argued that minority employees sometimes create facades of conformity that can result in emotional exhaustion and intentions to quit.…”
Section: Glbt Employees In Diversity and Voice Literaturesmentioning
confidence: 99%
“…40,41 This partially explains anticipatory aspects of stigma that are signaled by the often reported burden of managing information (or strategic disclosure), particularly about inconspicuous disorders. 42 The media has been shown to influence public stigma, particularly reinforcing negative stereotypes and promoting unfounded fear and precautionary responses. Extensive literature reviews on media portrayal of mental illness are available elsewhere.…”
Section: Antecedents Of Stigmamentioning
confidence: 99%
“…L'adoption d'une politique antidiscriminatoire qui prohibe clairement la discrimination et les comportements LGBTphobes s'avère une stratégie de base pour tout employeur (King et Cortina, 2010 ;Tejeda, 2006), à condition que tous soient informés de son existence. Cependant, les politiques à elles seules ne suffisent pas pour transformer les comportements et les attitudes négatives des employé.e.s et doivent s'accompagner d'autres types d'initiatives, par exemple des formations abordant la diversité sexuelle et de genre (Beatty et Kirby, 2006 ;Harding et Peel, 2007). Le changement organisationnel doit être global.…”
Section: Recommandations Pour Les Milieux Du Travailunclassified